Pengaruh Service quality Terhadap Kepuasan Nasabah Bank Syariah - Norvadewi Norvadewi; Akhmad Nur Zaroni (Al-Tijary, 2019)
Service quality is closely related to customer satisfaction. Intense competition makes banking a susceptible industry to customer service and satisfaction. Service quality will satisfy customers based on Islamic ethical values, especially in Islamic banking. This research aims to find out and analyze the effect of service quality on customer satisfaction of the Bank BRI Syariah Samarinda branch. This research is quantitative. The research data was obtained by disseminating questionnaires to BRI Syariah Samarinda branch customers, as many as 99 people, using accidental sampling techniques. Data analysis uses simple regression analysis. The results showed that service quality significantly affected customer satisfaction at the Bank BRI Syariah Samarinda branch. The magnitude of the determination coefficient value is 0.90, which means that the influence of service quality variables is 90%. Service quality significantly affects customer satisfaction, although other factors outside of this research affect customer satisfaction.